Operation and physics of photovoltaic solar cells: an overview - Noemi Guerra (Editorial Universitaria, 2018)
Solar energy is considered the primary source of renewable energy on earth; and among them, solar irradiance has both, the energy potential and the duration sufficient to match mankind future energy needs. Nowadays, despite the significant potential of sunlight for supplying energy, solar power provides only a very small fraction (of about 0.5%) of the global energy demand. In order to increase the worldwide installed PV capacity, solar photovoltaic systems must become more efficient, reliable, cost-competitive and responsive to the current demands of the market. In this context, PV industry in view of the forthcoming adoption of more complex architectures requires the improvement of photovoltaic cells in terms of reducing the related loss mechanism, focusing on the optimization of the process design, as well as, reducing manufacturing complexity and cost. Hence a careful choice of materials, a suitable architecture and geometric distribution, passivation techniques and the adoption of a suitable numerical modeling simulation strategy are mandatory. This work is part of a research activity on some advanced technological solutions aimed at enhancing the conversion efficiency of silicon solar cells. In particular, a detailed study on the main concepts related to the physical mechanisms such as generation and recombination process, movement, the collection of charge carriers, and the simple analytical 1D p-n junction model required to properly understand the behavior of solar cell structures. Additionally, the theoretical efficiency limits and the main loss mechanisms that affect the performance of silicon solar cells are explained.